2014
DOI: 10.1177/1066896914534466
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Human Chorionic Gonadotropin Expression in Recurrent and Metastatic Giant Cell Tumors of Bone

Abstract: Giant cell tumors of bone (GCTs) are generally benign, locally aggressive neoplasms that rarely metastasize. The beta subunit of human chorionic gonadotropin (beta-hCG) is expressed in syncytiotrophoblasts and several nongynecologic neoplasms but has not been described in GCT. At our institution, we observed cases of elevated beta-hCG in patients with GCT leading to diagnostic difficulty and in one case, concern for metastatic choriocarcinoma. This study aims to determine the frequency of beta-hCG expression i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Several previous studies have validated the abnormal expression of HCG in GCTB, bringing new hope for the exploration of potential biomarkers for GCTB [ 15 , 32 ]. As expected, our research also observed that HCG expression was decreased in clinical tissue samples from patients with GCTB, implying that HCG might be involved in the initiation of GCTB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have validated the abnormal expression of HCG in GCTB, bringing new hope for the exploration of potential biomarkers for GCTB [ 15 , 32 ]. As expected, our research also observed that HCG expression was decreased in clinical tissue samples from patients with GCTB, implying that HCG might be involved in the initiation of GCTB.…”
Section: Discussionmentioning
confidence: 99%
“…Lawless et al . demonstrated that β-HCG is abnormally expressed in serum samples of patients with recurrent and metastatic GCTB, implying that β-HCG might be a marker for GCTB [ 15 ]. As expected, our current studies indicated that HCG was lowly expressed in GCTB clinical samples and our further functional assays validated that HCG restrained the autophagy and EMT of GCTB stromal cells.…”
Section: Introductionmentioning
confidence: 99%
“…hCG is composed of two subunits: the α-subunit is similar to follicle-stimulating hormone, luteinizing hormone and thyroid-stimulating hormone, and the β-subunit provides the hormone's biological effects. hCG levels change during different phases of pregnancy [11]. To investigate the diagnostic value of β-hCG MoM in the early detection of PE, we undertook a meta-analysis-based approach, and our main results show that patients with PE exhibit a significantly higher serum level of β-hCG compared to normal pregnant women, indicating the high clinical value of β-hCG MoM in the early diagnosis of PE.…”
Section: Discussionmentioning
confidence: 99%
“…Aberrations in placental formation/function can initiate a chain of events, including increased serum β-hCG levels [8]. The serum level of β-hCG is also a diagnostic marker for hydatidiform moles, ovarian neoplasms, trophoblastic cancer, germ cell cancer and choriocarcinoma, non-gynecological diseases such as disorders of the testes, breasts, liver, lungs, colon and stomach as well as bone giant cell tumor and anaplastic thyroid carcinoma [9,10,11,12]. The main function of β-hCG in pregnancy is to protect the myometrial spiral arteries to allow the delivery of abundant nutrients to the placenta by maternal vessels [13].…”
Section: Introductionmentioning
confidence: 99%